Study on Influence Laws of Strata Behaviors for Shallow Coal Seam Mining beneath Gully Terrain - Zhiqiang Wang; Jingkai Li; Chao Wu; Wenyu Lv; Jiao Zhang; Peng Wang; Zhen Li; Hengzhe Qu (Shock and Vibration)
The study on influence laws of strata behaviors is the basic guarantee of safety mining for shallow coal seam beneath gully terrain. Taking 3302 mining face of Zhujiamao Coal Mine as the engineering background, the laws of strata behaviors for shallow coal seam mining beneath gully terrain are studied by field detection, theoretical analysis, and numerical simulation. The strata pressure observation and the hydraulic support working resistance show that the dynamic strata behaviors appear violently during mining beneath the gully bottom. The theoretical analysis shows that the rotation and breaking of key stratum beneath gully bottom under nonuniform load is the fundamental cause of strong dynamic strata behaviors. The numerical simulation of overburden movement and fissure development characteristics shows that the strata behaviors beneath the gully bottom are stronger than the strata behaviors beneath other areas. Additionally, according to the laws of dynamic strata behaviors, the safety measures for mining beneath gully bottom are put forward.